Trajectory of blood pressure, body mass index, cholesterol and incident dementia: systematic review. (January 2020) - Peters, Ruth; Peters, Jean; Booth, Andrew; Anstey, Kaarin J.
Abstract : Background: The global ageing population and the long prodromal period for the development of cognitive decline and dementia brings a need to understand the antecedents of both successful and impaired cognitive ageing. It is increasingly apparent that the trajectory of risk-factor change, as well as the level of the risk factor, may be associated with an increased or decreased risk of cognitive decline or dementia. Aims: Our aim was to summarise the published evidence and to generate hypotheses related to risk-factor trajectories and risk of incident cognitive decline or dementia. Method: We collated data from longitudinal observational studies relating to trajectory of blood pressure, obesity and cholesterol and later cognitive decline or dementia using standard systematic review methodology. The databases MEDLINE, Embase and PsycINFO were searched from inception to 26 April 2018. Results: Thirteen articles were retained for inclusion. Analytical methods varied. Our summary of the current evidence base suggests that first body mass index and then blood pressure rises and then falls more steeply in those who go on to develop dementia. The evidence for cholesterol was less consistent. Conclusion: Based on our review we present the hypothesis that weight falls around 10 years and blood pressure around 5 years before diagnosis. Confirmatory work is required. However, characterisation of risk according to combinations and patterns of risk factors may ultimately be integrated into the assessments used to identify those at risk of receiving a diagnosis of cognitive decline or dementia in late life.